Social media activities of hotels during COVID-19 pandemic: Case study based on the Facebook activities of three hotels in Visegrád, Hungary - Simon, Csilla; Pető, István (Acta Carolus Robertus, 2022)
Tourism has been an integral part of our lives for a long time and is a major economic sector. In 2019, the COVID-19 pandemic caused huge losses for the sector, with turnover almost completely lost during certain periods of the restrictions. In this study, we will examine through the example of a few hotels, how this period was reflected in social media used by individuals and businesses alike: Whether the hotels' Facebook communication changed (e.g. types of posts used, the number and textual content of posts), to what extent they engaged in "crisis communication" and how their followers reacted.
Keywords: social media; tourism; COVID-19; text analysis